The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.7589/0090-3558-22.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Spirochetes in Ticks and Antibodies to Borrelia Burgdorferi in White-Tailed Deer From Connecticut, New York State, and North Carolina

Abstract: Ticks were screened for spirochetes and serum samples from white-tailed deer (Odocoileus virginianus) were assayed for antibodies to Borrelia burgdorferi during 1983-1984. Using fluorescein isothiocyanate-labeled rabbit antibodies produced to B. burgdorferi, the etiologic agent of Lyme disease, spirochetes were detected in Ixodes dammini (10.5% of 1,193) and Dermacentor albipictus (0.6% of 157) adults from Connecticut, I . dammini nymphs (49.1% of 108) and adults (64.7% of 99) from Armonk, New York, and in I .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
55
1

Year Published

1988
1988
1996
1996

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(63 citation statements)
references
References 3 publications
7
55
1
Order By: Relevance
“…By indirect immunoiluorescence tests, antibodies to B. burgdorferi were identified in white-tailed deer living in tick-infested areas. Ixodid ticks could transmit this spirochete to humans and wildlife (10). In a differing view point, Telford et al concluded that deer are not reservoirs for B. burgdorie ri (18) but that the animals are crucial determinants of the density and spatial distribution of the ticks (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By indirect immunoiluorescence tests, antibodies to B. burgdorferi were identified in white-tailed deer living in tick-infested areas. Ixodid ticks could transmit this spirochete to humans and wildlife (10). In a differing view point, Telford et al concluded that deer are not reservoirs for B. burgdorie ri (18) but that the animals are crucial determinants of the density and spatial distribution of the ticks (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…It seeks an animal host, obtains a blood meal, and molts to the adult stage, completing the 2-year life cycle. The antibodies to B. burgdorferi were identified in white-tailed deer from Connecticut, New York State, and North Carolina, and ixodid ticks could transmit this spirochete to humans and wildlife (10). In Japan, Ixodid ticks, I. ovatus, I. persulcatus, I. nipponensis, I. tanuki, I. acutitarsus, I. angustus and others were parasitic on various wild animals, and some cases of human infestation were reported (17).…”
mentioning
confidence: 99%
“…12 As many as 30% to 70% of nonlarval deer ticks in these areas may be infected with Borrelia burgdorferi. [3][4][5][6] Because unrecognized Lyme disease can have severe consequences, many physicians in high-prevalence areas routinely treat patients with a recent history of a tick bite with oral antibiotics in an attempt to prevent the development of infection. One double-blind placebo-controlled study of this practice failed to demonstrate a clear benefit with treatment, even though all study participants were bitten by I. dammini and tick infection rates were 30%.…”
Section: Introductionmentioning
confidence: 99%
“…dammini (= 7. scapularis Say Spielman, Clifford, Piesman & Corwin [Oliver et al 1993]) (Bosler et al 1983, Piesman et al 1986, Magnarelli et al 1987, /. scapularis (Magnarelli et al 1986), and Ixodes pacificus Cooley & Kohls (Burgdorfer et al 1985, Lane & Burgdorfer 1987, Schoeler & Lane 1993 have shown very low rates of passage of B. burgdorferi from infected females to their progeny (<3%). However, in Europe the transovarial transmission of B. burgdorferi in 7. ricinus is less well known , Stanek et al 1986.…”
mentioning
confidence: 99%